Off-label use and harmful potential of drugs in a NICU in Brazil: A descriptive study. Issue 1 (December 2016) - de Souza, Alcidésio; dos Santos, Djanilson; Rey, Luís; Medeiros, Marina; Vieira, Marta; Coelho, Helena
Abstract Background Neonates admitted to neonatal intensive care units (NICU) are exposed to a wide variety of drugs, most without any data on safety and efficacy. Objective: To describe the drugs prescribed to different groups of neonates hospitalized in a NICU, and to analyze off-label use and harmful potential of drugs, in terms of the potential risks. Methods This was a six-month retrospective cohort study of drug use in a NICU, with neonates who were inpatients for a period of over 24 hours, and using prescription data from electronic medical records. Drug information found in the package leaflets, in the British National Formulary for Children 2012–2013, and in the Thomson Micromedex database were compared. Drugs and excipients considered potentially harmful were evaluated according to the literature. Results One hundred ninety-two neonates were included in the study, with a mean gestational age (GA) of 33.3 weeks (SD ± 4.3), 75.0 % were preterm, with an average of 18.8 days of hospitalization (SD ± 18.1), and a total of 3617 neonates-day. 3290 prescriptions were registered, on average 17.1 prescriptions/neonate (SD ± 17.9) and 8.8 drugs/neonate (SD ± 5.9). The number of prescriptions and drugs was higher in neonates with GA <31 weeks (p <0.05). Anti-infectives for systemic use, blood, alimentary tract and metabolism drug groups were more frequent, varying according to the GA. Neonates (99.5 %) were exposed to unlicensed drugs (UL) and off label use (OL), more frequently in GA <28 weeks (p <0.05). Most OL drugs used were indicated for newborns. 15 potentially harmful drugs were used in more than 70 % of the neonates, and most were OL; exposure to harmful excipients occurred in 91.6 % of the neonates, a percentage even higher when considering immature neonates. Conclusions Immature neonates in a Brazilian NICU are exposed to a variety of OL, UL and potentially harmful drugs and excipients.